Tổng hợp, nghiên cứu phức chất của honmi, ecbi với L-tryptophan - Thiềng, Lê Hữu; Uyển, Nguyễn Trọng; Huân, Trương Thị (Vietnam Journal of Chemistry, 2014)
The complexes of some rare earth elements (Ho; Er) with L–tryptophane have been isolated in solid state. The complexes have the formula [Ln(tryp)3]Cl3..3H2O (Ln: Ho, Er). The structure of the complexes has been recognized by the elemental analysis, IR spectra, thermal analysis methods and electrical conductivity measurements. It was found that the L–tryptophane utilized amino nitrogen and carboxyl oxygen for bonding. Keywords: Complex, amino acid, L–tryptophane, rare earth element Holmium, Erbium